A Survey of Enhanced Recovery After Surgery Protocols for Cesarean Delivery in Serbia - Pujic, Borislava; Kendrisic, Mirjana; Shotwell, Matthew; Shi, Yaping; Baysinger, Curtis L. (Frontiers in Medicine, 2018)
Enhanced recovery after surgery (ERAS) protocols have been described for patients undergoing colon surgery. Similar protocols for Cesarean Delivery (CD) have been developed recently. CD is one of the most commonly performed surgical procedures, and adoption of ERAS protocols following CD might benefit patients and the health care system. We aimed to determine which Serbian hospitals reported ERAS protocols, which elements of ERAS protocols were used in CD patients, and weather ERAS and non-ERAS hospitals differed. Survey was sent to all hospitals with obstetric services and 46 of 49 responded. The questionnaire asked whether ERAS protocols had been formally adopted for surgical patients and about their use in CD patients. Specific questions on elements described in other obstetric ERAS protocols for CD included preoperative patient preparation, type of anesthesia and temperature monitoring used for CD, maternal/neonatal contact, and time to discharge. ERAS protocols are used in 24% of surveyed hospitals, 84% admit the patient the day before elective CDs, 87% use a maternal bowel preparation morning on the day of CD, and 80% administer maternal deep venous thrombosis (DVT) prophylaxis. Only 33% remove IV in the first postoperative day, and 89% of women do not eat solid food until the day following their CD. Neuraxial anesthesia (NA) is used in 46% of elective CDs in ERAS hospitals compared to 9% in non-ERAS hospitals (p<0.01), and neuraxial narcotics for post CD analgesia are given more often in ERAS hospitals. Thirty-six percent of ERAS patients are discharged within 3 days, vs. none in non-ERAS group. Few elements of ERAS protocols reported from other centers outside Serbia are employed in Serbian hospitals performing CD. Despite significant changes that have been made recently in CD care, enhanced recovery after CD could be significantly improved in Serbian hospitals.